MENINGKATKAN KEMAMPUAN INTERAKSI SOSIAL SISWA AUTIS MELALUI PERMAINAN "GOBAK SODOR" DALAM BIMBINGAN KELOMPOK - Fifi Khoirul Fitriyah, (Psikologi Pendidikan dan Bimbingan, 2010)
The purpose of this study is to know whether there is a significant increase the social interaction ability score of autism students after the use of ¡§Gobak Sodor¡¨ game in group guidance. This research uses a one-group pretest-posttest design. The subject of this research is two autistic students in inclusive school of SMP Galuh Handayani Surabaya selected with a purposive sample technique. The reason the researchers chose subjects of this study is that two students had lower social interaction ability. In addition, they do not have a personality disorder characterized by the following characteristics: excessive dependence, and excessive fear, deep sadness, exploitative behavior, uncontrolled anger, and if their problems are handled they will not be satisfied. Data collection technique of this research uses observation and data analysis uses the sign test. Result of data analysis showed that £l > Ö or 1 > 0.05 so that Ho is refused and Ha is reseived, it can be concluded that the research hypothesis is accepted or there is a significant increase in score of social interaction skills of autism students after the use ¡§Gobak Sodor¡¨ game in group guidance.